(NkAZKI(B-(NGORO[INKI (B:s (NDLQ MOLOD[OGO [K)QÆLXNOGO WÆKU (B/s)E - (NsAWKA(B, )Qæ(NRINA(B,s)E; (NsAWKA(B, (NmAR(B'(NQNA(B,s; (NaN)QÆKÆNA(B, (NnATALÆQ(B,s)E ((NlXW)QÆW (B:s)E (NwIDAWNICTWO sTAROGO lEWA(B,s, 2020)
(NkOROTENXK)QÆ KAZKI PRO DRUVBU Æ PÆDTRIMKU(B, (NWINAHÆDLIWÆSTX Æ PRACEL@BNÆSTX(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NkAZKIs -- (NuKRA)QÇNAs)E; (NDRUVBAs; (NP)QÆDTRIMKAs)E; (NWINAH)QÆDLIWÆSTXs)E; (NPRACEL@BN)QÆSTXs)E